Maternal-fetal fluid balance and aquaporins: from molecule to physiology - Sha Xiao-yan; Xiong Zheng-fang; Liu Hui-shu; Di Xiao-dan; Ma Tong-hui (Acta Pharmacologica Sinica, 2016)
Maternal-fetal fluid balance is critical during pregnancy, and amniotic fluid is essential for fetal growth and development. The placenta plays a key role in a successful pregnancy as the interface between the mother and her fetus. Aquaporins (AQPs) form specific water channels that allow the rapid transcellular movement of water in response to osmotic/hydrostatic pressure gradients. AQPs expression in the placenta and fetal membranes may play important roles in the maternal-fetal fluid balance.